1996
DOI: 10.1007/bf00233153
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of a fruit tree, Morus australis Poir. syn. M. acidosa Griff.

Abstract: High frequency bud break and multiple shoots were induced in nodal explants collected between November to February from a 5 year old tree of Morus australis Poir syn. M. acidosa Griff. on Murashige and Skoog's medium supplemented with 6-benzylaminopurine (1.0 mg/1). Incorporation of gibberellic acid (0.3 mg/l) along with BAP (1.0 mg/l) not only induced faster bud break from nodal explants as well as from apical shoot buds, but it also enhanced the frequency of bud break. Nodal explants were more responsive tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…All these studies have reported the best multiplication of apical bud on MS basal medium supplemented with different concentrations of cytokinins only. Also, a similar situation was also noticed by Santamaria (Pattnaik et al, 1996). On the other hand, Gogoi et al (Gogoi & Borua, 2017) reported that supplementation of the MS medium with 1.5 mg/l of gibberelic acid (GA 3 ) improved elongated shoots of Morus indica L. (K2-cultivar).…”
Section: Discussionsupporting
confidence: 66%
“…All these studies have reported the best multiplication of apical bud on MS basal medium supplemented with different concentrations of cytokinins only. Also, a similar situation was also noticed by Santamaria (Pattnaik et al, 1996). On the other hand, Gogoi et al (Gogoi & Borua, 2017) reported that supplementation of the MS medium with 1.5 mg/l of gibberelic acid (GA 3 ) improved elongated shoots of Morus indica L. (K2-cultivar).…”
Section: Discussionsupporting
confidence: 66%
“…However, further increase in AdSO 4 inhibited all three of the responses mentioned above and the level of inhibition was proportional to the increase in the concentration of AdSO 4 (Table 1). Pattnaik et al (1996), in their experiments with Morus australis micropropagation, have also noticed that higher concentrations of cytokinins elicited inhibitory effects on shoot elongation. The basal medium supplemented with 4.92 mM IBA induced a higher percentage of rooting (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…A reduction in the number of shoots higher than the optimal level was earlier reported in other medicinal plants including Capsicum annum L. (Ahmad et al, 2006). Higher concentration of cytokinin elicited inhibitory effects on shoot elongation was also earlier reported by Pattnaik et al (1996). Regenerated leafy shoots derived from the nodal segments are introduced to triple auxins combinations for rooting.…”
Section: Resultsmentioning
confidence: 52%